Sedimentation and redispersibility of magnetorheological suspensions while settling under gravity. (31st July 2018) - Niu, Fang-Hao; Hu, Zhi-De; Yan, Hua; Zhang, Han-Song; Yang, Jian-Jian
Abstract: This work reports an investigation into the sedimentation stability and redispersibility of magnetorheological suspensions (MR suspensions). By applying a freeze sectioning method, slices of suspension layer were taken from a suspension column with minimum changes to shear history. The descent of the mudline was tracked, and the size distribution of particles contained in the suspension layer was studied using a laser scattering method. Oscillatory and steady shear was employed in studying the rheological flow behavior and viscoelasticity. Hydrodynamic force and particle interactions which have significant influence on those properties were analyzed in this study. In addition, indexes corresponding to sedimentation stability and redispersibility were put forward to make a quantitative comparison between three kinds of traditional MR suspension. The result shows that oleic acid could improve the sedimentation stability to a certain extent and hinder the formation of 'stiff cake', while nano-silica could significantly lower the sedimentation ratio but require considerable energy consumption to redisperse the suspension.